2013
DOI: 10.4103/0972-124x.118324
|View full text |Cite
|
Sign up to set email alerts
|

Massive pregnancy gingival enlargement: A rare case

Abstract: Gingival enlargement related to pregnancy is sometimes seen in the oral cavity. Pregnancy is a physiological state that brings full of changes in a woman's life. The metabolism and immunology of the body are modified by progesterone and estrogen as well as other local factors, these sex hormones may modify the oral mucosa and may lead to various periodontal diseases. A case of female patient 23 yrs of age reported during 8th month of pregnancy with a localised gingival enlargement affecting the buccal aspect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
(11 reference statements)
0
4
0
Order By: Relevance
“…Dack did show rough relationships between P int and the polarizability α of solvent molecules and of ced – P int with their dipole moments. Srivastava reported a relationship of the internal pressures of liquids to their normal boiling points P int = 4.5 [ 24.5 false( T normalb / normalK false) 1400 ] / V Suryanarayana and Pillai related the vapor pressure p ( T ) of 30 liquids, both dipolar and nonpolar, to their internal pressures log nobreak0em.25em⁡ p = a b P int where a and b are substance-specific coefficients that are independent of the temperature. Water and 1-propanol were outliers from this linear dependence.…”
Section: Internal Pressure Of Pure Liquidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dack did show rough relationships between P int and the polarizability α of solvent molecules and of ced – P int with their dipole moments. Srivastava reported a relationship of the internal pressures of liquids to their normal boiling points P int = 4.5 [ 24.5 false( T normalb / normalK false) 1400 ] / V Suryanarayana and Pillai related the vapor pressure p ( T ) of 30 liquids, both dipolar and nonpolar, to their internal pressures log nobreak0em.25em⁡ p = a b P int where a and b are substance-specific coefficients that are independent of the temperature. Water and 1-propanol were outliers from this linear dependence.…”
Section: Internal Pressure Of Pure Liquidsmentioning
confidence: 99%
“…The procedure was repeated stepwise to obtain the required data. It was found that the pressure was substantially linear with temperature, so that the slope of its dependence (Δ P/ Δ T at constant volume) represented γ V . This method determines the internal pressure P int = Tγ V – P directly and can be carried out with high accuracy, provided corrections are applied for compression of the containing vessel, amounting to 1–2% of the observed value …”
Section: Introductionmentioning
confidence: 99%
“…Only [IrCl 6 ] 3− have been considered as the only reactive species. Sheila et al 22 also reported IrCl 6 3− as the reactive species in oxidation reaction.…”
Section: Reacting Species Of Iridiummentioning
confidence: 97%
“…(9) Some authors believe that changes of estrogen levels in blood and saliva leads to changes in oral soft tissues. (8,10,11) It has been suggested that PV may be hormone (estrogen)-mediated and if this hypothesis is confirmed, hormone therapy can be beneficial. (5) Therefore, the present study aimed to evaluate ER expression in patients with oral and cutaneous PV without evaluating specific receptor types due to limited data on the exact location of ERs and the indefinite mechanism of estrogen signaling pathway.…”
Section: Introductionmentioning
confidence: 99%